Green or Grey? Goats, Economy and Ecology in Nkayi District, Zimbabwe: 1980–2017. (15th September 2019) - Kwashirai, Vimbai; Mhike, Ivo
This study explores the economic and ecological importance of goats in Nkayi District, Matabeleland North, Zimbabwe, 1980–2017. It evaluates the significance of goats in sustaining Ndebele rural livelihoods, debating whether goats are environmentally constructive or destructive. Nkayi is the foremost goat-producing region in Zimbabwe. Its semi-tropical and generally arid climatic features make it prone to periodic droughts. Nkayi is the ideal case study for examining the goat economy and ecology because of its diversity in environment and varied rural livelihoods. This study privileges analysis of primary data collected from semi-structured oral interviews with goat-keeping farmers, chiefs and contemporary reports as well as secondary sources – journal articles and books. Interviews were conducted in five areas of Nkayi District: Dopota, Fanisoni, Majaha, Madliwa and Vukuzenele (Dofamavu). The study adopts case study and sustainable livelihoods approaches focusing on goat farmers' perceptions of their animals' impact on the environment as well as the role that goats play in their livelihoods. Approximately 97 per cent of Zimbabwe's 3.5-million-goat herds are owned by small-holder farmers raising goats mostly for home consumption, and many of them are women. The study evaluates the degree to which rural livelihoods from farming are economically and ecologically sustainable in the medium-to-long-term in a drought-prone area of southern Africa.